A comparison of anterior cruciate ligament - Return to sports after injury (ACL-RSI) scores of male athletes nine-months Post-ACL reconstruction with matched uninjured controls. (July 2019) - Phelan, B.; King, E.; Richter, C.; Webster, K.; Falvey, E.
Abstract: Objectives: To report ACL-RSI scores in healthy athletes with no history of ACL injury. To measure ACL-RSI scores at nine-months post-ACL reconstruction and to assess the difference between healthy athlete and patient responses. Design: Cross-sectional study. Setting: Private sports clinic. Participants: 499 ACL reconstruction athletes completed the scale as they returned for their nine-month post-operative review appointment. A matched control group of 103 healthy athletes were selected for comparison. Main outcome measures: ACL-RSI for participants with controls completing a study-specific modified scale. Results: The median response to the ACL-RSI for the control group was higher (80.0) (Interquartile Range (IRQ) 66.7–88.3) than that of the ACL reconstruction group (74.17) (IRQ 59.2–86.0), however the effect size was small (0.1). Conclusion: This study reports normative values for uninjured athletes using the ACL-RSI questionnaire giving a benchmark for recovery after ACLR but also reflecting awareness of injury risk in uninjured athletes. ACL-RSI scores nine-months post-operatively had not yet returned to levels seen in matched uninjured controls. Highlights: First research to illustrate matched control responses to the ACL-RSI scale. Shows control athletes do not exhibit perfect scores the ACL-RSI. Small magnitude difference remains between controls and athletes nine-months post-ACLR.